PERAN STRATEGIS FILSAFAT ISLAM DALAM PENGEMBANGAN KAJIAN PSIKOLOGI ISLAM - Abidin, Muhammad Zainal (Jurnal Ilmiah Ilmu Ushuluddin, 2009)
This article tries to explore the strategic role of Islamicphilosophy in developing psychological studies. There are two ways todevelop psychological studies. First, studies based on Islamic tradition,and second studies based on modern psychology. The former is usuallycalled âIslamic psychologyâ which is based on traditional Islamicknowledge like Islamic philosophy and Sufism, while the latter is calledâpsychology of Islamâ which is based on certain elements of modernpsychology considered in line with Islamic values. In fact, both kinds ofpsychological studies are important if we want to put Islam andpsychology together.